2020
DOI: 10.1155/2020/3852586
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome Profiling across Five Tissues of Giant Panda

Abstract: Gene differential expression studies can serve to explore and understand the laws and characteristics of animal life activities, and the difference in gene expression between different animal tissues has been well demonstrated and studied. However, for the world-famous rare and protected species giant panda (Ailuropoda melanoleuca), only the transcriptome of the blood and spleen has been reported separately. Here, in order to explore the transcriptome differences between the different tissues of the giant pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…As one of the main components of blood clots, fibrinogen plays an important role in hemostasis. Mutations in FGA are related to renal amyloidosis ( Li F. et al, 2020 ). In CKD patients, the upregulation of MYC and FGA is one of the reasons for the aggravation of renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the main components of blood clots, fibrinogen plays an important role in hemostasis. Mutations in FGA are related to renal amyloidosis ( Li F. et al, 2020 ). In CKD patients, the upregulation of MYC and FGA is one of the reasons for the aggravation of renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that more stable results of transcriptome comparisons of giant pandas can be obtained by increasing the sample size to more than 5 (Li et al . 2020). In the present experiment, hair follicles were collected from different areas on 3 healthy pandas, and RNA samples were successfully extracted from them.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the rarity of samples from this species, most experiments are limited to samples collected from dead bodies or the analysis of metabolites in specimens such as blood, urine, and feces to study the adaptability and genetic diversity of giant pandas (Li et al . 2020; Ma et al . 2020; Wu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The giant panda reference genome has provided insight to their unique innate and cellular immunity. RNAseq was used to obtain transcriptomic information for the giant panda’s heart, liver, lung, and kidneys and was compared to previous transcriptome information for the blood and spleen [ 26 ]. Expression profiles associated with immunity revealed that breeding male giant pandas displayed enhanced innate immunity and cellular immunity with lower humoral immunity compared to non-breeding males, and identified 45 immune-related genes with altered expression (mostly up-regulated) [ 27 ].…”
Section: Reference Genomes Have Revealed Biomedical Relevancementioning
confidence: 99%